Inverse Distance Weight Spatial Interpolation for Topographic Surface 3D Modelling - mulkal razali; risa wandi; nurul aflah (TECHSI - Jurnal Teknik Informatika, 2019)
AbstractTopographic modelling is an important aspect in engineering work and planning such as dam design, road planning, volumetric calculation, water flow analysis and so forth. To get topographic data, usually a land survey or topographic measurement is taking for a region or an area under study. A number of points that represent an area are measured to get a height dataset. The dataset which is consist of height points will be used to model topographic condition of the area with generating contour map and also 3D model. There are some methods can be used to generate topographic surface in 3D model like linear interpolation in Triangular Irregular Network (TIN), Kriging and Inverse Distance Weight (IDW). This research implemented IDW spatial interpolation algorithm to model earth surface or topographic model in 3D. The IDW method was implemented in Python programming language using Numpy library for computation and Plotly graphic library to visualize the 3D Model.  Using 2500 and 10000  interpolation points with 100 random sampling points that extracted from Digital Surface Model (DSM), IDW was successfully estimated the height at unsampled locations. The results show, more higher interpolation point number will produce more detail surface texture.  Keywords : IDW, Topographic, 3D Modelling